Antioxidative potential of ferulic acid phenoxyl radical. (February 2020) - Amić, Ana; Marković, Zoran; Dimitrić Marković, Jasmina M.; Milenković, Dejan; Stepanić, Višnja
Abstract: The vast majority of previous studies dealing with antioxidant potency of (poly)phenols does not investigate the fate of phenoxyl radical obtained after single free radical scavenging. We investigated possible pathways of inactivation of ferulic acid phenoxyl radical (FAPR) using DFT method. Direct coupling with a set of 10 physiologically important free radicals, H-atom donation and dimerization were analysed by estimation of Gibbs free energy changes related to these processes. The former two processes are thermodynamically feasible to inactivate more dangerous free radicals such as hydroxyl, alkoxyl and carbon-centered radicals. Among dimerization reactions, the least energy demanding is formation of C-5−C-5 dimer of ferulic acid (FA), which has higher antiradical potency than FA itself. Obtained results reveal that FAPR, a priori considered as stable and unreactive, may contribute to the overall antioxidant activity of FA. This is a beneficial behavior, which makes FA a particularly valuable protector against oxidative stress. Hence, the contribution of phenoxyl radicals to the antioxidant activity of (poly)phenolic compounds should be taken into account, what has been scarcely considered until now. Graphical abstract: Image 1 Highlights: The fate of ferulic acid phenoxyl radical (FAPR) was thermodynamically investigated. The nature of scavenged free radicals influences FAPR reactivity. FAPR may undergo coupling with free radicals, dimerization and H-atom donation. C-5 site of FAPR is the most reactive site for radical attack. C-5−C-5 dimer of FAPR is the most stable.